Варіативність управлінської діяльності в сфері розвитку людських ресурсів і механізми її адаптації в транзитивній економіці - Рижакова, Г. М. (Ways to Improve Construction Efficiency, 2012)
In the article the four general approaches to human resources administration and development that showed themselves in the countries of the world have been defined. The forecast of the achievement time of ideally defined development of human resources status has been brought on the indices of human development of the United Nations Development Programme (UNDP). Variable directions of administrative activity in the sphere of human resources development in the conditions of globalization for different groups of the world countries have been worked out.